Review of The Women Who Ruled China: Buddhism, Multiculturalism, and Governance in the Sixth Century - Buckelew, Kevin (JAOS, 2025)
The Women Who Ruled China: Buddhism, Multiculturalism, and Governance in the Sixth Century. By Stephanie Balkwill. University of California Press. Pp. xx + 262. $34.95 (paper); open access.